Consumption Risk, Technology Adoption, and Poverty Traps : Evidence from Ethiopia - Dercon, Stefan; Christiaensen, Luc (World Bank, Washington, DC, 2012)
Much has been written on the determinants of input and technology adoption in agriculture, with issues such as input availability, knowledge and education, risk preferences, profitability, and credit constraints receiving much attention. This paper focuses on a factor that has been less well documented-the differential ability of households to take on risky production technologies for fear of the welfare consequences if shocks result in poor harvests. Building on an explicit model, this is explored in panel data for Ethiopia. Historical rainfall distributions are used to identify the counterfactual consumption risk. Controlling for unobserved household and time-varying village characteristics, it emerges that not just ex-ante credit constraints, but also the possibly low consumption outcomes when harvests fail, discourage the application of fertilizer. The lack of insurance causes inefficiency in production choices.